Simultaneous Election of Head of Custom Village - Bakarbessy, Andress Deny (Faculty of Law, Universitas Pattimura, 2022)
Introduction: The study in this paper is to analyze the involvement of custom villages in simultaneous village head elections.Purposes of the Research: to study and analyze whether custom village head elections can be carried out in conjunction with holding village head elections simultaneously.Methods of the Research: The research method used is normative research with a statutory approach and a conceptual approach.Results of the Research: The results show that simultaneous village head elections in villages and custom villages in SBB Regency can be carried out together. Where, the election process is carried out for villages based on the provisions of the Minister of Home Affairs regulation regarding village head elections, while the appointment of the head of the customary village government can be done if the candidate provided by the clan who has the right to govern is 1 (one) person, while the candidate for the head of the customary village government is more than 1 (one) there are candidates, then elections can be carried out while prioritizing the candidate for the head of government who has the right to govern based on customary rights or rights of origin.